Collaborative model development increases trust in and use of scientific information in environmental decision-making. Issue 82 (April 2018) - Ulibarri, Nicola
Highlights: Does the way models are developed affect their subsequent use in decision-making? The iterative, collaboratively-developed model became a core tool for negotiations. The consultation-based model was not used. Collaborative model development helped build the model's salience and credibility. Abstract: While science matters for environmental management, creating science that is credible, salient to decision-makers, and deemed legitimate by stakeholders is challenging. Collaborative modeling is an increasingly-used approach to enable effective science-based decision-making. This work evaluates the modeling process conducted for two hydropower dam licensing negotiations, to explore how differences in the collaborative development of hydrological models affected differences in their use in subsequent decision-making. In one case, the model was developed iteratively through deliberation with stakeholders. Consequently, stakeholders understood the model and its limitations and trusted the model and modelers; the model itself was also better designed to evaluate resource managers' questions. The collaboratively-developed model became the focal point for subsequent negotiations and enabled creative group problem-solving. Conversely, in the case with less engagement during model development, the model was not used subsequently by decision-makers. These differences are argued to result from trust built during the modeling process, applicability of the model to test real management scenarios, and the broader social context in which the models were used.